2014
DOI: 10.1002/2013jc009669
|View full text |Cite
|
Sign up to set email alerts
|

Feedbacks between ice cover, ocean stratification, and heat content in Ryder Bay, western Antarctic Peninsula

Abstract: A multiyear, all-season time series of water column physical properties and sea ice conditions in Ryder Bay, at the western Antarctic Peninsula (WAP), is used to assess the effects on the ocean of varying ice cover. Reduced ice cover leads to increased mixing and heat loss in the winter. The reduction in stratification persists into the following summer, preconditioning the water column to a greater vertical extent of surface-driven mixing. This leads to an increased amount of heat from insolation being mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 42 publications
4
66
1
Order By: Relevance
“…The monitoring site is situated in Ryder Bay, which is part of the northern Marguerite Bay region. Venables and Meredith () showed that the RaTS location in Ryder Bay is representative of the broader physical environment across northern Marguerite Bay. The distance between the nearest shore and the RaTS site is ∼2 km, and the maximum depth is ∼520 m. Data were collected between April 1997 and October 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The monitoring site is situated in Ryder Bay, which is part of the northern Marguerite Bay region. Venables and Meredith () showed that the RaTS location in Ryder Bay is representative of the broader physical environment across northern Marguerite Bay. The distance between the nearest shore and the RaTS site is ∼2 km, and the maximum depth is ∼520 m. Data were collected between April 1997 and October 2012.…”
Section: Methodsmentioning
confidence: 99%
“…We define fast‐ice cover as days with ≥ 80% coverage of the area by fast‐ice. Even though multiple observers throughout the years can introduce internal heterogeneity in the series due to the observations' subjective nature, such errors were still smaller than the large interannual variability in physical changes within the region (Venables and Meredith ).…”
Section: Methodsmentioning
confidence: 99%
“…thrived. Period 3 was characterized by increased wind mixing causing a more homogenous water column and deeper MLDs, typical for conditions at the end of summer and observed more frequently at the WAP Montes-Hugo et al, 2009;Venables and Meredith, 2014;Rozema et al, 2017b). Thereafter, the community consisted of large proportions of haptophytes, diatoms and cryptophytes (Figure 6).…”
Section: Influence Of Presence/absence Of Sea Ice On Phytoplankton Dymentioning
confidence: 97%
“…Here, the year-round Rothera Oceanographic and Biological Time Series (RaTS) program, representing the larger northern Marguerite Bay region, provides the infrastructure and scientific context to understand the dynamics in phytoplankton productivity (Venables and Meredith, 2014). Previous studies have shown a variable, yet generally high, level of phytoplankton biomass dominated by diatoms during summers in this region (Annett et al, 2010;Kozlowski et al, 2011;Rozema et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…They generally occur in shallow mixed layers where wind speeds are <5 m s −1 (Fitch and Moore, 2007). Storms, wind mixing, and waves deepen mixed depths in the MIZ, reducing the light availability and inhibiting bloom development ( Figure 7B) (Venables and Meredith, 2014). As a result, blooms only cover 17-24% of the MIZ over summer with maximum coverage of only 0.36 million km 2 in December (Savidge et al, 1996;Fitch and Moore, 2007).…”
Section: Marginal Ice Zonementioning
confidence: 99%